Insights into Tertiary Non-English Majors’ Self-Efficacy Beliefs and Anxiety in English Language Learning - Tran Quoc Thao; Nguyen Huynh Truc An (Tạp chí Khoa học Xã hội và Nhân văn (VNU Journal of Social Sciences and Humanities), 2026)
Self-efficacy (SE) in language learning in general and English language learning (ELL) in particular has been considered one of the vital psychological factors in the learning process, and it has a certain correlation with anxiety. Nevertheless, it is observed that different types of learners may have different characteristics of SE and anxiety. This quantitative study aims to scrutinize non-English majors’ SE beliefs and their anxiety in ELL. A group of 100 non-English majors were conveniently sampled from a Ho Chi Minh City-based institution in Vietnam to answer the questionnaires from which the gained data were processed by the SPSS software in terms of descriptive statistics and Pearson’s Correlation. The findings indicated that the participants felt anxious, and their level of SE beliefs in ELL was low. Moreover, non-English majors’ level of SE beliefs was negatively correlated with their anxiety in ELL. This study also discusses the pedagogical implications of the findings, which are hoped to increase non-English majors’ SE beliefs and reduce their anxiety in ELL, as well as shed light on future similar studies. Received 7th October 2022; Revised 11th March 2023; Accepted 29th March 2023